Original paperProstate brachytherapy in New South Wales: patterns of care study and impact of caseload on treatment quality - Thompson, Stephen R.; Delaney, Geoff P.; Gabriel, Gabriel S.; Izard, Michael A.; Hruby, George; Jagavkar, Raj; Bucci, Joseph; Barton, Michael B. (Journal of Contemporary Brachytherapy, 2014)
Purpose: We performed the first comprehensive, population-based brachytherapy (BT) Patterns of Care Study in the Australian setting. Herein we report on prostate BT and assess the technical quality of BT practice, focusing on whether a caseload effect could be identified in New South Wales (NSW). Material and methods : Site visits were made to all radiation oncology departments in NSW that delivered prostate BT, collecting relevant data on NSW residents treated with prostate BT in 2003. Overall quality of NSW prostate BT treatment was assessed using benchmarks including treatment of appropriate prostate cancer disease risk category, absence of (relative) physical contraindications, optimal planned and treated dosimetry, and pre/post-implant planning/CT. Quality was compared between higher and lower caseload departments. Results : One hundred and fifty-seven (67%) patients underwent temporary BT and 79 (33%) permanent seed BT. Prostate BT was concentrated in five departments, with three of four departments with active programmes treating greater than the recommended 25 cases. Rates of concordance with quality benchmarks were high (85-99%) with no consistent caseload effect identified. Conclusions : Prostate BT in NSW in 2003 was generally of high quality and a caseload effect on quality could not be identified. This may be because the number of departments was insufficient to determine a caseload effect, or because the prostate BT was largely concentrated in a small number of high caseload departments.